Penerapan Strategi Pembelajaran Konflik Kognitif dalam Mereduksi Miskonsepsi Siswa pada Materi Gelombang Bunyi (IPF: Inovasi Pendidikan Fisika, 2022)
A cognitive conflict learning strategy is a learning strategy in which students will be faced with situations where they will experience conflict with themselves regarding the new knowledge obtained with the knowledge they have so far. The purpose of this study was to determine the profile of students' misconceptions on the sound wave and to analyze the effect of applying cognitive conflict learning strategies in reducing students' misconceptions. The research method used in this study is a mixed-method explanatory sequential design with a quasi-experimental design and a non-equivalent control group design. The research data were then analyzed using a multiple-choice diagnostic test with reasoned CRI (Certainty of Response Index). The results of the study revealed that almost all students in the sample class had misconceptions in each of the sub-concepts of the sound wave. After learning, there was a decrease in the average misconception of students in the control class by 27.64% and a decrease in the average misconception of students in the experimental class by 39.90%. This shows that the application of cognitive conflict learning strategies has an effect on reducing students' misconceptions. Keywords: Cognitive Conflict Learning Strategies, Remediation, Misconception, Sound Wave.